The Implications for Regional Investment of Diversification Strategies in Commercial Real Estate Portfolios - Philip McCann; Stephen Lee (European Regional Science Association (ERSA), 2005)
A number of studies have examined the benefits of regional diversification strategies within commercial real estate portfolios with two approaches adopted; the first is based on primary contiguous geographical regions while the second employs areas based on economic function. In general, the conclusion is that diversifications strategies based on simple geographical areas adds little, if anything, while economic based regions have shown much greater potential. The economic regions approach to portfolio analysis appears to be a much more valuable tool in evaluating regional real estate investment opportunities and risks. The reason is that this method allows consistent risk measurement between aerial units and enables the portfolio manager to develop a geographically diversified portfolio through the use of economically cohesive regions. The aim of this paper is therefore to identify how the application of these portfolio investment techniques determines the flows of funds coming into regions, and the consequent impacts on regional investment in the regional built environment. Most previous research on this issue is based in the US with studies in other countries largely hampered by lack of real estate data and/or acceptable definitions of economic regions. This study therefore attempts to rectify this position in the UK using a large data set of real estate and socio-economic data.
Keywords: 330